2019
DOI: 10.3122/jabfm.2019.03.180338
|View full text |Cite
|
Sign up to set email alerts
|

Family Physicians' Contributions to Rural Emergency Care and Urban Urgent Care

Abstract: Using 2017 data, we demonstrate a sharp increase in the proportion of family physicians (FPs) working primarily in rural emergency departments and increasing numbers of FPs working in urgent care centers. Despite growth in emergency medicine-trained physicians, FPs are likely to continue to be the backbone of emergency care in rural America. (J Am Board Fam Med 2019;32:295-296.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As such, we likely slightly underestimate the number of actual FM EPs. 4,5 Second, we are unable to account for the contributions of osteopathic EPs. Data are linked only to ACGME and ABMS; there is no equivalent osteopathic database.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we likely slightly underestimate the number of actual FM EPs. 4,5 Second, we are unable to account for the contributions of osteopathic EPs. Data are linked only to ACGME and ABMS; there is no equivalent osteopathic database.…”
Section: Discussionmentioning
confidence: 99%
“…We found more EPs compared with 2008 but a decrease in the density of EPs in rural areas. 2,3 Further, we found that nearly a third of rural EPs reported prior family medicine (FM) residency training; 3 FM-trained EPs-who we will refer to as FM EPs-play an important role in emergency care in the rural United States, 4,5 but this population has not been well characterized. Our goal was to characterize the 2020 population of clinically active FM EPs and identify their geographic distribution.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a discussion of emergency medicine and primary care partnership to meet the shortage of rural EM physicians [ 13 , 14 ]. As the national emergency physician workforce study showed, only 52% of physicians in large rural and 37% in small rural are emergency medicine trained.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Rural EDs experience staffing challenges, infrequent patients with critical illness, and reduced access to specialists, leading to variable sepsis guideline adherence. [14][15][16][17][18] Many rural sepsis patients are transferred to other hospitals as part of their care, but even regionalized care does not fully reduce disparities in outcomes. 14,[19][20][21][22]…”
Section: Introductionmentioning
confidence: 99%